Upaya Guru Pai Dalam Meningkatkan Akhlak Peserta Didik Di Sma Darut Taqwa Kedung Rejoso Kotaanyar Probolinggo Tahun Pelajaran 2018 - Moch. Yunus; Rahayu, Indah (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
ABSTRACT The aim of national education is to develop the potential of students to become human beings who have faith and fear the Almighty God, have a noble character, are healthy, knowledgeable, capable, creative, independent and become democratic citizens in their social life in society including in educational institutions. SMA Darut Taqwa Kedung Rejoso Kotaanyar Probolinggo. There is a tendency that education has not been fully able to help in improving the morals of students which will shape students' personality development optimally. However, there are some moral deviations (morals) that still occur in educational institutions even though on a small scale, if allowed to continue it will be a domino effect on other students. In this case the teacher has a very important role in the world of education, especially in the field of education as well as guiding students to become human beings who have noble character to God and to others. Keywords: Teacher's Effort, Morals.